Analysis, Isolation, and Activation of Antigen-Specific CD4+ and CD8+ T Cells by Soluble MHC-Peptide Complexes - Schmidt, Julien; Dojcinovic, Danijel; Guillaume, Philippe; Luescher, Immanuel (Frontiers in Immunology, 2013)
T cells constitute the core of adaptive cellular immunity and protect higher organisms against pathogen infections and cancer. Monitoring of disease progression as well as prophylactic or therapeutic vaccines and immunotherapies call for conclusive detection, analysis and sorting of antigen-specific T cells. This is possible by means of soluble recombinant ligands for T cells i.e. MHC class I-peptide (pMHC I) complexes for CD8+ T cells and MHC class II-peptide (pMHC II) complexes for CD4+ T cells and flow cytometry. Here we review major developments in the development of pMHC staining reagents and their diverse applications and discuss perspectives of their use for basic and clinical investigations.